The Role of Technology in Determining Liability for Damages Caused by the Use of Peaceful Nuclear Energy - Izzat, Wafa (Journal of Legal Sciences, 2026)
Modern nuclear projects rely on digital systems, dense sensor networks, and data sharing tools. These tools can help show what happens when nuclear damage is claimed. They can also shape how the law assigns responsibility for that damage. Many nuclear liability systems already place strict liability on the operator and limit who can be sued. Even so, technology still matters because it affects proof, causation, and later recourse claims. Technology also matters when damage crosses borders and when cyber events play a role. This research explains how modern technology changes the way responsibility is found for nuclear damage from peaceful use. It reviews key liability treaties, state responsibility rules, and national examples. It then links those rules to radiation mapping, remote sensing, digital logs, and forensic methods. It also addresses cyber attribution and AI use in safety and operations. The research ends with practical steps that can improve fairness, speed, and trust in nuclear damage decisions.